Phenetic Diversity and Relationships of Sea Lettuce (Ulva spp.) on the Southern Coast of Gunungkidul Yogyakarta Indonesia - Abdul Razaq Chasani; Melinda Windiana Febrianti; Muhammad Said Rifqi (International Journal of Marine Engineering Innovation and Research, 2025)
The development of tourism areas in the Gunungkidul coastal zone was a potential threat that can affect the marine macroalgae diversity. In order to prevent the decline of macroalgae diversity from these anthropological threats, a comprehensive study is needed to record the population dynamics that occur. The objective of this study is revealing the species diversity and phenetic relationship of the sea lettuce (Ulva spp.). Phenetic analysis of sea lettuce was conducted by observing morphological, anatomical, and biochemical characters. Clustering analysis was done by the UPGMA method, whereas ordination analysis was conducted using the PCA (Principal Component Analysis) method; both of them were calculated using the MVSP 3.1 program. The result of the study discovered four species of Ulva, i.e., Ulva lactuca, Ulva rigida, Ulva compressa, and Ulva linza. The reconstruction of phenetic relationships revealed two main clusters of sea lettuce, exhibiting a percentage difference of 75.2. The PCA analysis exhibited eight characters that significantly influence clustering patterns, including thallus color, blade width, blade thickness, blade hole, stiff edge cells, cell surface diameter, elongated cell shape, and the presence of violaxanthin and neoxanthin.